Bacterial Microbiome in Wild-Caught Anopheles Mosquitoes in Western Thailand - Tainchum, Krajana; Dupont, Chloé; Chareonviriyaphap, Theeraphap; Jumas-Bilak, Estelle; Bangs, Michael J.; Manguin, Sylvie (Frontiers in Microbiology, 2020)
Among the complex microbial community living in the mosquito midgut, some bacteria can deliver effector molecules with anti-Plasmodium effects suppressing development of malaria parasites (Plasmodium falciparum) before the ookinete can invade the mosquito midgut epithelium, such as some Enterobacter species. Despite knowledge of this phenomenon, only a few studies have defined the diversity of microbiota in wild-caught malaria vector species. The objective of this study was to analyze and compare the bacterial diversity in different Anopheles species, including representatives of the main malaria vectors in northwestern Thailand. Wild populations of Anopheles species (non-infected and infected with malaria parasites) were sampled from malaria endemic areas in Tak and Mae Hong Son Provinces near the Thai-Myanmar border. Bacterial diversity was assessed by 16S rRNA gene, V3 hypervariable region, PCR-Temporal Temperature Gel Electrophoresis (PCR-TTGE) profiling and sequence analysis. A total of 24 bacterial genera were identified from eight Anopheles species. Five genera were detected from a single malaria (Plasmodium vivax) infected Anopheles minimus and were not observed in other non-infected mosquitoes. Seven genera are newly reported in Anopheles mosquitoes, including Aerococcus, Ferrimonas, Megasphaera, Pectobacterium, Peptostreptococcus, Shimwellia and Trabulsiella, suggesting that the abdominal bacterial diversity of Anopheles remains largely underestimated. Elizabethkingia sp., a relatively common midgut bacterium of Anopheles mosquitoes was also detected. 16S PCR-TTGE provides the first estimation of the abdominal bacterial biodiversity present in Anopheles in Thailand. Because microbiota might impact pathogen development in Anopheles and thereby reduce the risk of disease transmission, more studies are needed to understand the presence and biological role of bacteria in natural mosquito populations.